The Improvement of Nutrient Utilization and Performance in Laying Hens Fed By-Product Diets Supplemented with Xylanase and/or Protease Enzymes - Widjaja, H.; Nahrowi,; Jayanegara, A.; Utomo, D.; Hazen, K. (Tropical Animal Science Journal, 2025)
Diets formulated for laying hens often contain anti-nutritional factors—such as non-starch polysaccharides (NSPs), trypsin inhibitors, and phytate—that can impede nutrient absorption. To mitigate these effects and enhance feed efficiency, the poultry industry increasingly incorporates exogenous enzymes like xylanase and protease, either separately or synergistically, to improve the digestibility and nutritional value of by-product feed ingredients. This study was conducted to evaluate the effects of xylanase and/or protease enzyme supplementation in laying hen diets on nutrient digestibility and overall bird performance. Four distinct dietary treatments were formulated, including a negative control (NC) diet that did not contain any enzyme supplementation. The remaining three dietary treatments were modifications of the negative control (NC) diet, incorporating either xylanase, protease, or a combination of both enzymes (xylanase + protease). The NC diet was formulated to contain 2,567 kcal/kg of apparent metabolizable energy corrected for nitrogen (AMEn), 0.77% digestible lysine (dLys), and phytase supplementation. Performance trial showed that supplementation of protease and xylanase+protease had higher (p